Deterioration of Heart Rate Recovery Index in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD) - Ozveren, Olcay; Dogdu, Orhan; Sengul, Cihan; Cinar, Veysel; Eroglu, Elif; Kucukdurmaz, Zekeriya; Degertekin, Muzaffer (Int Scientific Literature, Inc, 2014)
Background: Non-alcoholic fatty liver disease (NAFLD) has been considered as a benign disease often associated with central obesity and insulin resistance and, in general, with factors of the metabolic syndrome. Heart rate recovery after exercise is a function of vagal reactivation, and its impairment is an independent prognostic indicator for cardiovascular and all-cause mortality. The aim of our study was to evaluate the heart rate recovery index in patients with NAFLD. Material/Methods: The study population included 59 patients with NAFLD (mean age=42.3 +/- 9.3 years) and 22 healthy subjects as controls (mean age=40.7 +/- 6.5 years). Basal electrocardiography, echocardiography, and treadmill exercise testing were performed on all patients and controls. The heart rate recovery index was defined as the reduction in the heart rate from the rate at peak exercise to the rate at the 1st minute (HRR1), 2nd minute (HRR2), 3rd minute (HRR3), and 5th minute (HRR5) after stopping exercise stress testing. Results: There were significant differences in HRR1 and HRR2 indices between patients with ED and the control group (19.9 +/- 8.2 vs. 34.1 +/- 9.6; p<0.001 and 24.3 +/- 5.4 vs. 40.5 +/- 9.1; p=0.006, respectively). Similarly, HRR indices after the 3rd and 5th minutes of the recovery period were significantly lower in patients with NAFLD compared with those indices in the control group (32.3 +/- 8.5 vs. 58.4 +/- 6.5; p=0.001 and 58 +/- 18.2 vs. 75.1 +/- 15.8; p<0.001). Effort capacity was markedly lower (11 +/- 1.9 vs. 12.5 +/- 1.5 METs; p=0.001) among the patients with NAFLD. Conclusions: The heart rate recovery index is deteriorated in patients with NAFLD. When the prognostic significance of the heart rate recovery index is considered, these results may help explain the increased occurrence of cardiac death. It points to the importance of the heart rate recovery index in the identification of high-risk patients.
Keywords: Autonomic Nervous System; Fatty Liver; Heart Rate